2015
DOI: 10.1007/s00345-015-1500-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of adherent perirenal fat on peri-operative outcomes of robotic partial nephrectomy

Abstract: During RPN, APF is associated with increased bleeding and a higher risk of conversion to open surgery and to radical nephrectomy. Male gender, hypertension, obesity, and MAP score are predictors of APF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
77
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 19 publications
12
77
4
3
Order By: Relevance
“…The higher rate of conversion to radical nephrectomy was the main weakness of the off-clamp technique, given the similar rates of postoperative complications between both groups. This comparable rate of postoperative complication was in line with previous series [17,18] and might be explained by the multifactorial determinants of postoperative complications after PN, which may be influenced by the surgical technique but also patient and tumor's characteristics, perirenal fat, or surgeon's experience [9,20] .…”
Section: Discussionsupporting
confidence: 73%
“…The higher rate of conversion to radical nephrectomy was the main weakness of the off-clamp technique, given the similar rates of postoperative complications between both groups. This comparable rate of postoperative complication was in line with previous series [17,18] and might be explained by the multifactorial determinants of postoperative complications after PN, which may be influenced by the surgical technique but also patient and tumor's characteristics, perirenal fat, or surgeon's experience [9,20] .…”
Section: Discussionsupporting
confidence: 73%
“…Our study is the first to evaluate the incidence of APF in Asian individuals with renal malignancy. The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12].…”
Section: Discussioncontrasting
confidence: 55%
“…The current results showed, however, that Asians had a lower incidence of APF at lower BMI levels compared to Caucasians. The predictors of APF other than MAP score reported in the Western cohorts were male gender, older age, obesity, waist circumference, and hypertension [3][4][5]. The current study indicated that male gender was a strong predictor of APF in multivariate analysis, although other metabolic factors, including older age, higher BMI, smoking habit, and history of hypertension were not associated with the presence of APF.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations